Duration oriented resource allocation strategy on multiple resources projects under stochastic conditions - Tereso, Anabela Pereira (2009)
Previous developments from the first author and other researchers were made on devising models for the total cost optimization of projects described by activity networks under stochastic conditions. Those models only covered the single resource case. The present paper will discuss the case of multiple resources. More precisely, we introduce a strategy of allocation of those resources in order to minimize the waste arising from their latent idleness on their consumption within the same activity. With this strategy we will start from the possible durations yielded by each resource and devise the allocation vector leading to equal durations.